Directive Speech Acts in Mark Twain’s The Adventure of Huckleberry Finn - Widyastuti Widyastuti; Endang Sartika (UIN Salatiga, 2023)
This research aims to explore Directive Speech Acts in the novel The Adventure of Huckleberry Finn by Mark Twain. This research used a descriptive qualitative method by employing literary pragmatics analysis. The object of this research was the utterances of the main characters in the novel's dialogue. The data were collected by reading the text closely, observing the dialogue in the text, note taking and highlighting the directive speech acts, coding and classifying the types of directive speech acts, then analyzing and interpreting the types of directive speech acts based on the theory proposed by Searle. There are five types of Directive Speech Acts found in this novel: asking, commanding, requesting, prohibiting, and advising. The data finding has shown that the highest type of asking is 160 utterances or 48,94 %. It is shown by Jim (a slave nigger), who always asks Huck Finn about everything. The second is commanding, with 112 utterances or 34,25%. The next type is requesting, with 28 utterances or 8,56%. Prohibiting has 18 utterances or 5,50%, and advice has the lowest portion, nine utterances or 2,75 %. The novel's directive speech acts play different functions, including asking for information and confirmation, asking someone to or not to do something, and suggesting. It also shows that directive speech acts such as asking, commanding, prohibiting, requesting, and advising have been influenced by social relations between the interlocutor, including social distance and social power.